Perceived Organizational Support and Diuwongke Attitude on Credit Officer Performance: Organizational Commitment as Mediator - Eriyanti Ahmar; Dedi Muhammad Siddiq; Acep Komara; James Champion Alick Tembo (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study supports Asta Cita’s Sixth Mission to strengthen Indonesia’s village and regional economies by examining the role of Rural Banks (BPRs) as drivers of rural financial inclusion and MSMEs development. Despite their strategic position, BPRs face increasing challenges, including rising non-performing loans, declining credit officer performance, and weakening organizational culture. This research investigates how perceived organizational support and the Javanese relational value diuwongke (treating others with dignity and humanity) influence organizational commitment and credit officers’ performance. A sequential explanatory mixed-methods approach was employed, integrating survey data from 145 credit officers across 11 BPRs in Region III Cirebon, analyzed using SEM-PLS, with in-depth interviews to contextualize the findings. The results show that both perceived organizational support and diuwongke significantly enhance commitment and performance, with organizational commitment mediating these relationships. The structural model explains approximately 44% of the variance in performance, indicating moderate explanatory power. Qualitative evidence further illustrates that support and cultural humanization foster psychological safety, loyalty, and affective engagement. The study highlights the need for empathetic and culturally grounded human resources practices to reinforce BPR resilience and sustain their developmental role in rural economies.